Методи математичного планування експерименту в інформаційному середовищі мікро- та наноелектронних систем - Головко, В. Д.; Стрілкова, Т. О. (ХНУРЕ, 2025)
A modern engineer, in his practical activity, is often forced to conduct experimental research that requires planning of experiments. Establishing the optimal conditions of the studied process is associated with the use of special mathematical methods. One such method, which has received intensive development in recent years, is the method of mathematical planning of experiments.
Keywords: планування експерименту; наноелектронна система